2015
DOI: 10.3390/nu7010277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Black Adzuki Bean (Vigna angularis) Extract on Proliferation and Differentiation of 3T3-L1 Preadipocytes into Mature Adipocytes

Abstract: The aim of this work was to investigate the effects of black adzuki bean (BAB) extract on adipocytes, and to elucidate the cellular mechanisms. In order to examine the proliferation of preadipocytes and differentiating adipocytes, cell viability and DNA content were measured over a period of time. Lipid accumulation during cell differentiation and the molecular mechanisms underlying the effects of BAB on the transcriptional factors involved, with their anti-adipogenic effects, were also identified. We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
(55 reference statements)
2
26
0
Order By: Relevance
“…Hypertrophy and hyperplasia lead to adipose tissue expansion, and hypertrophy occurs before hyperplasia in the progression of obesity (de Ferranti & Mozaffarian, ; Jo et al., ). The process where preadipocytes differentiate into lipid‐laden adipocytes is called adipogenesis, occurs in several stages, including preadipocyte cell proliferation, differentiation and lipid accumulation and transcription factors such as peroxisome proliferator activated receptor gamma (PPARγ) and CCAAT/enhancer binding proteins (C/EBPs) regulates this process (K. N. Kim et al., ; M. Kim, Park, Song, & Cha, ). Lipogenesis is the process of triglyceride (TG) synthesis, which requires enzymes including acetyl CoA carboxylase (ACC) and fatty acid synthase (FAS) (Sung et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertrophy and hyperplasia lead to adipose tissue expansion, and hypertrophy occurs before hyperplasia in the progression of obesity (de Ferranti & Mozaffarian, ; Jo et al., ). The process where preadipocytes differentiate into lipid‐laden adipocytes is called adipogenesis, occurs in several stages, including preadipocyte cell proliferation, differentiation and lipid accumulation and transcription factors such as peroxisome proliferator activated receptor gamma (PPARγ) and CCAAT/enhancer binding proteins (C/EBPs) regulates this process (K. N. Kim et al., ; M. Kim, Park, Song, & Cha, ). Lipogenesis is the process of triglyceride (TG) synthesis, which requires enzymes including acetyl CoA carboxylase (ACC) and fatty acid synthase (FAS) (Sung et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…BAB has previously been shown to inhibit lipid accumulation in adipocyte cells downregulating C/EBPβ , C/EBP α, and PPARγ expression (Kim et al ). Another study reported that adzuki beans stimulate phosphorylation of AMP activated protein kinase (AMPK), which may suppress ACC (Sato, Mukai, Kataoka, & Kurasaki ).…”
Section: Discussionmentioning
confidence: 99%
“…The BAB extract was freeze‐dried and ground into a powder. The composition of freeze‐dried BAB powder samples has been previously characterized (Kim et al ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations